2013
DOI: 10.4172/2157-7471.1000200
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Chemical Resistance Inducers Approaches for Controlling Foliar Diseases of Some Vegetables under Protected Cultivation System

Abstract: Different alternative approaches of antagonistic bio-agents, Trichoderma harzianum, T. Viride, Bacillus subtilis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
0
5
0
1
Order By: Relevance
“…The antifungal mechanism of essential oils might be related to the diffusion inside the cells, affecting cell membrane synthesis, mitochondrial function, DNA destruction, cell lysis, or inhibiting the sporulation and germination of spoilage fungi [14,89]. Previous studies on tomatoes and cherry tomatoes account for suitable antifungal activities of different chitosan-essential oil treatments [22][23][24]. Still, our present work demonstrates that low-temperature treatment, in combination with CS + RGEO treatments with a minimum of 1.0% of RGEO, were able to inhibit fungi growth on tomato fruits in situ completely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antifungal mechanism of essential oils might be related to the diffusion inside the cells, affecting cell membrane synthesis, mitochondrial function, DNA destruction, cell lysis, or inhibiting the sporulation and germination of spoilage fungi [14,89]. Previous studies on tomatoes and cherry tomatoes account for suitable antifungal activities of different chitosan-essential oil treatments [22][23][24]. Still, our present work demonstrates that low-temperature treatment, in combination with CS + RGEO treatments with a minimum of 1.0% of RGEO, were able to inhibit fungi growth on tomato fruits in situ completely.…”
Section: Discussionmentioning
confidence: 99%
“…Although several chitosan-essential oil strategies have been reported to control fungal decay of tomatoes, many of them were applied during preharvest stages, with severe complications in the growth of the tree leaves. On the other hand, few studies have been addressed during the postharvest stage directly [21][22][23][24][25][26]. However, some of them were applied to cherry tomatoes, and others did not show complete fungal inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Both ISR and SAR increased productions of proteins (defense enzymes) like peroxidase (PO), pathogenesis related (PR), phenylalanine ammonia lyase (PAL), polyphenol oxidase (PPO), phenols etc. (Jones and Dangl, 2006;Walters et al, 2009), which showed positive associations with resistance for several fungal diseases of vegetable and legume crops (Vallad and Goodman, 2004;Abdel-Kader et al, 2013). In mungbean, limited studies have been conducted to understand the mechanism of ISR and SAR.…”
Section: Botanical Fungicides and Bio-stimulantsmentioning
confidence: 99%
“…The induced resistance (IR) can be activated by a number of substances, preventing or delaying the entry or subsequent activity of the pathogen in their tissues (Abdel-Kader et al, 2013;Shah et al, 2014). Several agents can induce the production of "signs" in plant tissues, triggering reactions that culminate in a lasting protection against a wide range of pathogens.…”
Section: Defence Mechanismsmentioning
confidence: 99%